Clinical findings and prognosis of patients hospitalized for acute decompensated heart failure: Analysis of the influence of Chagas etiology and ventricular function. - Caíque Bueno Terhoch; Henry Fukuda Moreira; Silvia Moreira Ayub-Ferreira; Germano Emilio Conceição-Souza; Vera Maria Cury Salemi; Paulo Roberto Chizzola; Mucio Tavares Oliveira; Silvia Helena Gelas Lage; Edimar Alcides Bocchi; Victor Sarli Issa (Public Library of Science (PLoS), 2018)
Explore the association between clinical findings and prognosis in patients with acute decompensated heart failure (ADHF) and analyze the influence of etiology on clinical presentation and prognosis.Prospective cohort of 500 patients admitted with ADHF from Aug/2013-Feb/2016; patients were predominantly male (61.8%), median age was 58 (IQ25-75% 47-66 years); etiology was dilated cardiomyopathy in 141 (28.2%), ischemic heart disease in 137 (27.4%), and Chagas heart disease in 113 (22.6%). Patients who died (154 [30.8%]) or underwent heart transplantation (53[10.6%]) were younger (56 years [IQ25-75% 45-64 vs 60 years, IQ25-75% 49-67], P = 0.032), more frequently admitted for cardiogenic shock (20.3% vs 6.8%, P<0.001), had longer duration of symptoms (14 days [IQ25-75% 4-32.8 vs 7.5 days, IQ25-75% 2-31], P = 0.004), had signs of congestion (90.8% vs 76.5%, P<0.001) and inadequate perfusion more frequently (45.9% vs 28%, P<0.001), and had lower blood pressure (90 [IQ25-75% 80-100 vs 100, IQ25-75% 90-120], P<0.001). In a logistic regression model analysis, systolic blood pressure (P<0.001, OR 0.97 [95%CI 0.96-0.98] per mmHg) and jugular distention (P = 0.004, OR 1.923 [95%CI 1.232-3.001]) were significant. Chagas patients were more frequently admitted for cardiogenic shock (15%) and syncope/arrhythmia (20.4%). Pulmonary congestion was rare among Chagas patients and blood pressure was lower. The rate of in-hospital death or heart transplant was higher among patients with Chagas (50.5%).A physical exam may identify patients at higher risk in a contemporaneous population. Our findings support specific therapies targeted at Chagas patients in the setting of ADHF.